PERUBAHAN POLA TRANSFORMASI PENDIDKAN ISLAM DI BAWEAN DARI MASA KEMASA - Adnan, Mohammad (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2022)
Education is something that must develop towards a better and more advanced, both in all its aspects. Education is a constructive form of building superior human resources, both physically, spiritually, pedagogically and others. Therefore, education should be the spearhead in building the nation's human resources. Therefore, the development of education needed here is from all aspects. Therefore, education on the island of Bawean inevitably must be able to harmonize with the development of education both in terms of the system and others. This needs to be done because education must be in line with the development of technological advances. So that the system that is built must also run in a straight line with the existing conditions. Educational transformation is indeed important in response to the challenges of future civilization. Bawean with all its limited access, inevitably must also proceed properly so that in all fields of education, both formal and non-formal, must move towards progress, including in the world of Islamic boarding school education on the island of Bawean. Keywords: transformation pattern, bawean education